Environmental data and microorganism composition from the HAVOC sea ice ridge study during the MOSAiC expedition (PS122) in the Central Arctic Ocean 2019-2020 - Oliver Müller; Jessie Gardner; Lasse Mørk Olsen; Evgenii Salganik; Philipp Assmy; Rolf Gradinger; Gunnar Bratbak; Clara Jule Marie Hoppe; Benjamin Allen Lange; Morven Muilwijk; Dmitry V Divine; Nicole Aberle; et al. (PANGAEA, 2025)
This dataset gives an overview of environmental data including temperature, salinity, brine volume fraction (for sea ice only), dissolved nutrients, particulate organic carbon and nitrogen, particulate elemental concentration, as well as chlorophyll a concentrations, bacterial production and the abundance of microorganisms either enumerated using light microscopy (organisms between 20 μm – 300 μm) or flow cytometry (FCM for organisms smaller than 20 μm) of HAVOC sea ice ridge specific samples, taken during the Multidisciplinary drifting observatory for the study of Arctic Climate (MOSAiC) during leg 2, 3 and 4 (December 2019 – August 2020). Additional expedition and sampling details can be found in the ECO-overview paper (Fong et al., 2024). We thank all persons involved in the expedition of the Research Vessel Polarstern during MOSAiC in 2019-2020 (AWI_PS122_00) as listed in Nixdorf et al. (2021). The yearlong MOSAiC ice drift (October 2019 to September 2020), with the research vessel Polarstern serving as the base, started in the eastern Eurasian Basin and crossed the Amundsen and Nansen basins towards the Fram Strait (Fong et al., 2024). One dedicated research project (Ridges - Safe HAVens for ice-associated flora and fauna in a seasonally ice-covered Arctic Ocean (HAVOC) (Granskog and Müller, 2024) performed detailed and interdisciplinary observations of ridges during MOSAiC. During the drift, three different ridges were sampled at different times of the year. The changes between ridges were necessary, as logistical challenges and ice dynamics prevented the sampling of the same ridge throughout the entire period (see below), highlighting the difficulties associated with studying ridges. The first ridge (R1) was investigated in winter, the second ridge (R2) was investigated in spring, and the third ridge (R3) was investigated in summer. Based on their macrostructural physical properties, the three ridges were similar in characteristics. They formed during the MOSAiC drift (similar age) and were composed of thin ice blocks, with similar sail heights (1–2 m) and average keel depths (3.2–4.3 m). Ice cores for temperature and salinity measurements as well as biogeochemical variables were extracted with a 9-cm (Mark II) internal diameter ice corer (Kovacs Enterprise, USA). Ice temperature was measured in situ using a Testo 720 thermometer in drill holes with a length of half-core diameter at 5–10 cm vertical resolution. Ice bulk salinity was measured from melted ice core sections using a YSI 30 conductivity meter (the conductivity is converted to salinity and reported on the Practical Salinity Scale 1978, PSS-78, which is dimensionless). The relative brine volume fraction of each section was calculated following Cox and Weeks (1983) and Leppäranta and Manninen (1988) for in situ conditions using the ice temperature profile measured in the field and the bulk salinities. Ice cores collected for biogeochemical variables were cut into 10 cm long sections in the field and collected in sterile plastic bags, with the focus on the three habitats: the ice of the roof and the floor of water-filled voids, the bottom of the ridge, and, when present, the frozen void and algae inclusions. Biogeochemical variables were, when possible, derived from pooled ice core sections of three replicate cores (R3), and during challenging weather periods (R1 and R2) from single ice cores. The core sections were kept dark and cool, transferred to the lab on board and melted in the dark after the addition of filtered seawater: 50 mL 0.22 μm filtered seawater was added per cm of sea ice thickness, and the sea ice samples melted within 24–36 hours in the dark at around 4°C. When possible, the water (20–30 L) inside the voids, below the ridge and below level ice, was sampled using a manual bilge pump with a silicon tube with a diameter of 20 mm into prewashed polyethylene containers. From both melted sea ice and water samples, sub-samples were taken for determination of inorganic nutrients, biogenic silica (BSi), particulate organic carbon (POC), elemental composition of particles (XRF), chlorophyll a (Chl-a), bacterial production (BP) and abundance and diversity estimates of protists and bacteria through flow cytometry (FCM), light microscopy, as described in more detail below. Nutrient analysis was performed using colorimetric techniques with an AA3 continuous flow auto analyzer (Seal Analytical), following GO-SHIP protocols. Samples from Jan–May 2020 were analyzed onboard; Jun–Jul samples were frozen and analyzed later. Biogenic and lithogenic silica (BSi & LSi) were quantified using a more laborious time-course digestion protocol which uses 0.1 molar sodium carbonate (as done previously for turbid Arctic coastal water samples in Varela et al. 2016) and allows for better isolation of the BSi signal from the solubilized LSi. Particulate organic carbon (POC) was filtered (0.3–2 L) onto pre-combusted GF/F filters, frozen, acid-fumed, and analyzed via CHN analyzer. Elemental composition was assessed by filtering 0.25–1 L onto polycarbonate filters and total particulate concentrations of P, S, O, Si, Fe and Mg were measured by wavelength dispersive X-Ray fluorescence spectroscopy (WDXRF) using a Bruker® AXE S4 pioneer XRF instrument. Chlorophyll a (Chl-a) was extracted from filtered samples using 90% acetone and measured fluorometrically on a calibrated Turner Design 10-AU fluorometer (Turner Designs, USA), including an acidification step (1 M HCl) to determine phaeopigments (Knap et al., 1996). Protists were identified and counted using inverted light microscopy after preservation with a Lugol-formalin mixture. Samples were settled for 48 hours in Utermöhl chambers and grouped into four main groups (diatoms, dinoflagellates, ciliates and other flagellates). Bacterial production was estimated by incubating samples with tritiated leucine at in situ temperature, followed by TCA fixation and centrifugation. Radioactivity was counted on a Perkin Elmer Liquid Scintillation Analyzer Tri-Carb 2800TR, and leucine incorporation was converted to carbon production using established conversion factors (Simon and Azam, 1989). Flow cytometry was used to quantify phytoplankton, heterotrophic nanoflagellates (HNF), and bacteria from water and melted sea ice samples fixed with glutaraldehyde and stored at -80°C. Phytoplankton were analyzed using an Attune® flow cytometer, with fluorescence-based identification; bacteria and HNF were stained with SYBR Green I and analyzed on a FACS Calibur. Names of size groups of photosynthetic and heterotrophic organisms are in accordance to "Standards and Best Practices For Reporting Flow Cytometry Observations: a technical manual (Version 1.1)" (https://repository.oceanbestpractices.org/handle/11329/2111.2). A short summary is listed here: RedPico = picophytoplankton (1-2 μm); RedNano = Nanophytoplankton (2-20μm), which includes subgroups RedNano_small (2-5 μm), RedNano_large (5-20 μm); OraPico = Nanophytoplankton with more orange fluorescence; OraNano = Cryptophytes; OraPicoProk = Synechococcus; HetNano = heterotrophic nanoflagellates; HetProk = bacteria (and when present archaea); HetLNA = low nucleic acid (LNA) containing bacteria; HetHNA = high nucleic acid (HNA) containing bacteria with the subgroups HetProk_medium = HNA-bacteria subgroup with less fluorescence signal, HetProk_large = HNA-bacteria subgroup with more fluorescence signal and HetProk_verylarge = HNA-bacteria subgroup with very strong fluorescence signal; Virus = virus-like particles, including size refined subgroups: LFV (low fluorescence virus or small virus); MFV (medium fluorescence virus or medium virus); HFV (high fluorescence virus or large virus) according to Larsen et al., 2008